Extension Information Delivery Methods: Detecting Trends Among Users - John G. Richardson (Journal of Applied Communications, 1989)
The primary purpose of this study was to (a) determine what communications channels are used by agricultural producers who obtain information from the North Carolina Agricultural Extension Service; (b) identify the five most frequently used channels for receiving Extension information at the present time; and (c) determine what channels farmers expect to use most frequently in the future.